Interleukin-22 Signaling in the Regulation of Intestinal Health and Disease - Parks, Olivia B.; Pociask, Derek A.; Hodzic, Zerina; Kolls, Jay K.; Good, Misty (Frontiers in Cell and Developmental Biology, 2016)
Interleukin (IL)-22 is a member of the IL-10 family of cytokines that has been extensively studied since its discovery in 2000. This review article aims to describe the cellular sources and signaling pathways of this cytokine as well as the functions of IL-22 in the intestine. In addition, this article describes the roles of IL-22 in the pathogenesis of several gastrointestinal diseases, including inhibition of inflammation and barrier defense against pathogens within the intestine. Since many of the functions of IL-22 in the intestine are incompletely understood, this review is meant to assess our current understanding of the roles of IL-22 and provide new opportunities for inquiry to improve human intestinal health and disease.